Oral hygiene level objectification in preventive screening of patients with ENT-organs pathology using digital optical diagnostics methods - Prikuls, V.F.; Karneeva, O.V.; Kim, I.A.; Alexandrov, M.T.; Kukushkin, V.I.; Prikule, D.V. (Clinical Dentistry (Russia), 2020)
Chronic nose and paranasal sinuses pathology is given special attention in the structure of upper respiratory tract infections. The interaction between oral diseases activity and clinical evidence of ENT-organs pathological processes is revealed. The objective of the study is to determine the effectiveness of digital optical raman-fluorescent diagnostics based on biosolids of teeth hard tissues and saliva tests to optimize personal oral hygiene methods and exclude the potentiation of ENT-organ diseases progression of odontogenic etiology. Materials and methods. 23 patients with various diseases of ENT-organs aged 19 to 54 have been chosen (17 females and 5 males), to be tested for the level of hygiene. Fluorescent diagnostics has been performed with the hardware/software system “InSpektrM” using the contact and stable technique of influence with the low-intensive laser radiation wavelength of 365 nm given at right angle to a surface of a crown part of teeth. Oral fluid examination at before and after tooth brushing stages has been performed with means of raman-fluorescent diagnostics and excitation radiation wave length of 532 nm. Results. High efficiency of fluorescent diagnostics method is established at determining the level of oral hygiene. It is revealed that the patients with previously noted satisfactory hygiene level have maximum decrease in fluorescence intensity by 10 times (from 35,000 to 3,000 relative units) after 3 minutes of teeth brushing. The patients with a good level of hygiene have minimum decrease in intensity by 4 times (from 13,000 to 3,000 relative units) after three minutes teeth brushing. There is no reliably proof to further reduction of radiation intensity by increasing the brushing up to 5—7 minutes.